Tenofovir Alafenamide for Pregnant Chinese Women With Active Chronic Hepatitis B: A Multicenter Prospective Study - Zeng, Qing-Lei; Zhang, Hong-Xu; Zhang, Ji-Yuan; Huang, Shuo; Li, Wei-Zhe; Li, Guang-Ming; Pan, Ya-Jie; Feng, Ying-Hua; Li, Zhi-Qin; Zhang, Guo-Fan; Xu, Jiang-Hai; Lin, Wan-Bao; et al. (Clinical gastroenterology and hepatology, 2022)
Data on long-term tenofovir alafenamide (TAF) therapy for pregnant women with active chronic hepatitis B (CHB) (immune clearance and reactivation phases, currently and previously diagnosed) and their infants are lacking. Pregnant women with active CHB treated with TAF and tenofovir disoproxil fumarate (TDF) were enrolled in this multicenter prospective study, and infants received immunoprophylaxis. The primary outcomes were rates of adverse (safety) events in pregnant women and defects in infants and fetuses. The secondary outcomes were virologic responses in pregnant women, infants’ safety, hepatitis B surface antigen (HBsAg) status, and growth conditions. One hundred three and 104 pregnant women were enrolled and 102 and 104 infants were born in the TAF and TDF groups, respectively. In the TAF group, the mean age, gestational age, alanine aminotransferase level, and viral loads at treatment initiation were 29.3 years, 1.3 weeks, 122.2 U/L, and 5.1 log10 IU/mL, respectively. TAF was well-tolerated, and the most common adverse event was nausea (29.1%) during a mean of 2 years of treatment. Notably, 1 (1.0%) TAF-treated pregnant woman underwent induced abortion due to noncausal fetal cleft lip and palate. No infants in either group had birth defects. In the TAF group, the hepatitis B e antigen seroconversion rate was 20.7% at postpartum month 6, infants had normal growth parameters, and no infants were positive for HBsAg at 7 months. The TDF group had comparable safety and effectiveness profiles. TAF administered throughout or beginning in early pregnancy is generally safe and effective for pregnant women with active CHB and their infants. [Display omitted]